Review of Design Innovations and Efficiency in Hydraulic Valve Control Systems - Kumar, Sree Biddut; Acharjee, Partho Protim; Hossen, Md Saim; Basak, Pallab (Peneliti Teknologi Teknik Indonesia, 2025)
This paper explores the evolution and innovations in hydraulic valve control systems, emphasizing their role, technological advancements, and current challenges. Hydraulic valves are essential components in regulating fluid flow, pressure, and direction within hydraulic systems, and are widely used in industries such as aerospace, automotive, manufacturing, and mobile machinery. Recent innovations in valve materials, miniaturization, and intelligent control systems have significantly enhanced the design and operational efficiency of hydraulic systems. The integration of electro-hydraulic, proportional, and servo control technologies has improved precision and adaptability in managing fluid dynamics. These developments have led to notable gains in energy efficiency, system reliability, and performance. The introduction of digital control systems and machine learning has further expanded possibilities, enabling real-time monitoring, predictive maintenance, and remote- control capabilities. Despite these advancements, challenges remain particularly in addressing high material costs, integration complexities, and the ongoing need for more energy-efficient solutions.